2009
DOI: 10.1007/s10661-009-0797-9
|View full text |Cite
|
Sign up to set email alerts
|

Determination of organochlorine pesticide and polychlorinated biphenyl levels in adipose tissue of infertile men

Abstract: During the recent two decades, a remarkable drop in fertility rates has been noticed almost all over the world. A series of studies have showed that environmental factors had the primary role causing the observed adverse trends in the male reproductive health problems. Especially chlorinated hydrocarbons, for instance polychlorinated biphenyls (PCB) and pesticides, could mimic or antagonize the effects of steroid hormones, like estrogens and androgens and possibly interfering with male reproductive capacity. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Animal studies have also shown similar effects of PCBs on sperm motility and number [89]. High levels of PCB 52 and PCB 180 were found in the adipose tissue of fertile and infertile men, suggesting their participation in the disease [90]. Maternal exposure to PCBs can also cause a wide range of developmental and reproductive disorders in male newborns, such as cryptorchidism (undescended testes) and hypospadias [91].…”
Section: Resultsmentioning
confidence: 88%
“…Animal studies have also shown similar effects of PCBs on sperm motility and number [89]. High levels of PCB 52 and PCB 180 were found in the adipose tissue of fertile and infertile men, suggesting their participation in the disease [90]. Maternal exposure to PCBs can also cause a wide range of developmental and reproductive disorders in male newborns, such as cryptorchidism (undescended testes) and hypospadias [91].…”
Section: Resultsmentioning
confidence: 88%
“…Almost all of the methylciva in the food passes into the blood. Nervous system, brain damage and kidneys on the heavy damage, recurrent miscarriage, nervous system development disorders in children, has been determined by studies that cause stillbirths [18].…”
Section: Introductionmentioning
confidence: 99%
“…7 Exposure to PCBs is of public health relevance because animal and human studies have demonstrated their cancer and non-cancer effects. Chronic exposure to PCBs at lower doses negatively impacts the nervous, immune, and reproductive systems, and human studies have shown effects on memory, learning, IQ, and motor function in children, 1821 fertility in adults, 22,23 and immune system suppression in children and adults. 2426 Animal studies have demonstrated cancers of the liver, thyroid, and immune system, 2729 and occupational studies have found associations with liver and biliary tract cancers.…”
Section: Introductionmentioning
confidence: 99%